Penerapan Prinsip Manajemen Kelas Dan Pengaruhnya Terhadap Motivasi Belajar Bahasa Indonesia Siswa Kelas II SD Negeri 24 Macanang Kabupaten Bone - Rukayah Rukayah; Abd. Kadir (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The purpose of this study is to describe the application of classroom management principles and explain their effect on the motivation to learn Indonesian in second grade students at SD 24 Macanang, Bone Regency. This research is a qualitative research. Research participants came from two classes, namely class 2A and class 2B which consisted of two teachers and 34 students. The research was carried out through three stages, namely preparation, implementation, and data collection. Data collection techniques used are interview, observation, questionnaire, and document analysis. The validity of the research data using triangulation techniques. The data collected were analyzed using interactive data analysis techniques. The results showed that the application of classroom management principles at SD 24 Macanang, Bone Regency was well implemented. Through the application of these classroom management principles, students' motivation to learn Indonesian is high. This can be seen from the behavior of students as follows: (1) there is student activity in learning; (2) the willingness of students to try things that are difficult; (3) the students' desire to succeed; (4) the willingness of students to start learning activities from themselves; (5) students survive when facing learning difficulties; (6) the students' attention to the teacher's explanation. Based on the results of this study, it can be concluded that the application of classroom management principles has an effect on the motivation to learn Indonesian in second grade students of SD 24 Macanang, Bone Regency.